A multicenter cross-sectional survey of the role of community pharmacists, attitudes, and perceptions in preventing and controlling cardiovascular diseases - Nthabiseng Florina Motlohi; Kofi Boamah Mensah; Neelaveni Padayachee; Ruwayda Petrus; Saleh F. Alqifari; Varsha Bangalee (PLoS ONE, 2025)
Background Cardiovascular diseases are a leading cause of mortality globally and impose suffering and economic difficulties, particularly in low- and middle-income countries. Community pharmacists present an opportunity for effective prevention and control of cardiovascular diseases. The overarching aim of the study was to evaluate factors associated with the extent of involvement, barriers and facilitators, and perceptions of Lesotho community pharmacists in preventing and controlling cardiovascular diseases. Methods The study utilised a quantitative cross-sectional survey. A semi-structured questionnaire was distributed to licensed community pharmacists across four districts between March and July 2023. Parametric and non-parametric tests were performed for data analysis using a Statistical Package for Social Sciences version 26. Results Apart from medicine dispensing, community pharmacists were mostly involved in hypertension (mean = 4.38±.73) and diabetes (mean = 4.17±.91) screening, weight management advice (mean = 3.81±.87), disease education (mean = 3.93±.83), medication management therapy (mean = 3.74±.99, 3.81±.88), referral of and follow up on patients (mean = 3.70±.98 and 3.87±.92). There was a significant association between the extent of involvement and pharmacy location, experience of community pharmacists, availability of tools, number of patients seen daily, and presence of other healthcare professionals at a community pharmacy (p<0.05). The most common barriers were related to patient factors (>75% agree to strongly agree), such as lack of awareness of community pharmacists’ services. Community pharmacists possessed positive (mean >3) attitudes and perceptions regarding their role in cardiovascular disease management. Conclusions Besides dispensing medicine, community pharmacists had varying extent of involvement in health promotion activities. The provision of these services differed between socio-demographic groups. Community pharmacists possessed good knowledge, positive attitudes towards their cardiovascular disease management role. Thus, they can improve cardiovascular disease outcomes. However, the barriers potentially limit their scope of practice and encourage inconsistent community pharmacy services. The findings present pertinent information to policy-makers, regulators, and pharmacists that can inform the development of frameworks to improve clinical and pharmacy practice in Lesotho and low- and middle-income countries.